1977
DOI: 10.1104/pp.59.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ethylene and Carbon Dioxide Evolution during Cotton Explant Abscission

Abstract: The relationship between abscission and the evolution of ethylene and CO2 was examined in explants and explant segments of cotton seedlings (Gossypium hirsutum L. cv. Acala SJ-1) under both static and flow system conditions, and in the presence and absence of mercuric perchlorate. Explant excision was immediately followed by increased ethylene evolution (wound ethylene); senescence was also accompanied by increased ethylene evolution (senescence ethylene Cotton plants have provided the materials for extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The increased respiration rate from 4 days before FB is probably related to the increased ethylene production during FB and flower abscission. Similar results have been found in cotton explant abscission (Marynick 1977) and coleus explants (Reid 1985). However, the increased rates of respiration during the 2nd week AFB may be partially a result of the early fruit development.…”
Section: Discussionsupporting
confidence: 76%
“…The increased respiration rate from 4 days before FB is probably related to the increased ethylene production during FB and flower abscission. Similar results have been found in cotton explant abscission (Marynick 1977) and coleus explants (Reid 1985). However, the increased rates of respiration during the 2nd week AFB may be partially a result of the early fruit development.…”
Section: Discussionsupporting
confidence: 76%
“…However, although physiological roles remain to be determined, increases in peroxidase activity in the AZ during the onset of abscission are well documented ( Hinman and Lang, 1965 ; Gahagan et al , 1968 ; Henry, 1975 ; McManus, 1994 ). Oxidative reactions are thought to be essential for abscission ( Marynick, 1977 ) and antioxidant treatments are able to reduce significantly abscission rates under certain conditions ( Michaeli et al , 1999 ). In addition, peroxidases may be involved in the coordination of gene expression in response to pathogens ( Sexton and Roberts, 1982 ).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in peroxidase activity in the abscission zone during the onset of abscission are well documented ( Hinman and Lang, 1965 ; Gahagan et al , 1968 ; Henry, 1975 ) although their roles in the process of abscission are still unclear. Marynick (1977) concluded that oxidative respiration is essential to trigger abscission, while Michaeli et al (1999) demonstrated that whole plant antioxidant treatments significantly reduced low temperature-induced leaf abscission in Ixora coccinea . On the other hand, Sexton and Roberts (1982) , proposed that peroxidases may be involved in the co-ordination of gene expression in response to pathogens.…”
Section: Discussionmentioning
confidence: 99%